Pengaruh Net Profit Margin, Return on Assets dan Debt Equity Ratio Terhadap Effective Tax Rate Pada Subsektor Makanan dan Minuman Yang Terdaftar di BEI - Kasir (Jurnal Riset Bisnis dan Investasi, 2022)
The purpose of this study was to determine the effect of profitability (NPM, ROA) and leverage (DER) on tax avoidance (ETR) in food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the period 2012-2019. The data used is secondary data. The regression model used is multiple regression analysis. The results of this study using a t-test showed that both net profit margin and return on assets had an effect on the effective tax rate, but the debt to equity ratio had no effect on the effective tax rate. The F (simultaneous) test states that the net profit margin, return on assets and debt to equity ratio simultaneously affect the effective tax rate, with the coefficient of determination showing a simultaneous effect of 28.6%. While the remaining 71.4% is influenced by other factors not included in this study, such as return on equity, and sales growth.